The Properties of the Transient Outward, Inward Rectifier and Acetylcholine-Sensitive Potassium Currents in Atrial Myocytes from Dogs in Sinus Rhythm and Experimentally Induced Atrial Fibrillation Dog Models - Zsófia Kohajda; Claudia Corici; Attila Kristóf; László Virág; Zoltán Husti; István Baczkó; László Sághy; András Varró; Norbert Jost (Pharmaceuticals, 2024)
Aims: Atrial fibrillation (AF) is the most common chronic/recurrent arrhythmia, which significantly impairs quality of life and increases cardiovascular morbidity and mortality. Therefore, the aim of the present study was to investigate the properties of three repolarizing potassium currents which were shown to contribute to AF-induced electrical remodeling, i.e., the transient outward (Ito), inward rectifier (IK1) and acetylcholine-sensitive (IK,ACh) potassium currents in isolated atrial myocytes obtained from dogs either with sinus rhythm (SR) or following chronic atrial tachypacing (400/min)-induced AF. Methods: Atrial remodeling and AF were induced by chronic (4–6 weeks of) right atrial tachypacing (400/min) in dogs. Transmembrane ionic currents were measured by applying the whole-cell patch-clamp technique at 37 °C. Results: The Ito current was slightly downregulated in AF cells when compared with that recorded in SR cells. This downregulation was also associated with slowed inactivation kinetics. The IK1 current was found to be larger in AF cells; however, this upregulation was not statistically significant in the voltage range corresponding with atrial action potential (−80 mV to 0 mV). IK,ACh was activated by the cholinergic agonist carbachol (CCh; 2 µM). In SR, CCh activated a large current either in inward or outward directions. The selective IK,ACh inhibitor tertiapin (10 nM) blocked the outward CCh-induced current by 61%. In atrial cardiomyocytes isolated from dogs with AF, the presence of a constitutively active IK,ACh was observed, blocked by 59% with 10 nM tertiapin. However, in “AF atrial myocytes”, CCh activated an additional, significant ligand-dependent and tertiapin-sensitive IK,ACh current. Conclusions: In our dog AF model, Ito unlike in humans was downregulated only in a slight manner. Due to its slow inactivation kinetics, it seems that Ito may play a more significant role in atrial repolarization than in ventricular working muscle myocytes. The presence of the constitutively active IK,ACh in atrial myocytes from AF dogs shows that electrical remodeling truly developed in this model. The IK,ACh current (both ligand-dependent and constitutively active) seems to play a significant role in canine atrial electrical remodeling and may be a promising atrial selective drug target for suppressing AF.